The impact of zinc supplementation on morbidity from diarrhea and respiratory infections among rural Guatemalan children - Ruel, Marie T.; Rivera, Juan A.; Santizo, Maria-Claudia; Lonnerdal, Bo; Brown, Kenneth H. (American Academy of Pediatrics, 1997)
Objective. A community-based, randomized, double-blind intervention trial was conducted to measure the impact of zinc supplementation on young Guatemalan children's morbidity from diarrhea and respiratory infections.Methods. Children aged 6 to 9 months were randomly assigned to receive 4 mL of a beverage containing 10 mg of zinc (as zinc sulfate) daily (7 d/wk) for 7 months (n = 45) or a placebo (n = 44). Morbidity data were collected daily. Diagnoses of diarrhea, fever, and anorexia were based on mothers' definitions. Respiratory infections were defined as the presence of at least two of the following symptoms: runny nose, cough, wheezing, difficulty breathing, or fever.Results. High rates of diarrhea and respiratory infections were reported. Children from the placebo group had a 20% episodic prevalence of diarrhea, with 8 episodes/100 d, and a 7% episodic prevalence of respiratory infections, with 3 episodes/100 d. The median incidence of diarrhea among children who received zinc supplementation was reduced by 22% (Wilcoxon rank test), with larger reductions among boys and among children with weight-for-length at baseline lower than the median of the sample (39% reductions in both subgroups). Zinc supplementation also produced a 67% reduction in the percentage of children who had one or more episodes of persistent diarrhea (χ2 test). No significant effects were found on the episodic prevalence of diarrhea, the number of days per episode, or the episodic prevalence or incidence of respiratory infections.Conclusions. The large impact of zinc supplementation on diarrhea incidence suggests that young, rural Guatemalan children may be zinc deficient and that zinc supplementation may be an effective intervention to improve their health and growth.